Nano-scale elastic-plastic properties and indentation-induced deformation of single crystal 4H-SiC - Nawaz, A.; Mao, W.; Lu, Chunsheng; Shen, Y. (Elsevier, 2017)
The nanoscale elastic-plastic response of single crystal 4H-SiC has been investigated by nanoindentationwith a Berkovich tip. The hardness (H) and elastic modulus (E) determined in the load-independent region were 36±2 GPa and 413±8 GPa, respectively. The indentation size effect (ISE) of hardness within an indentation depth of 60 nm was systematically analyzed by the Nix-Gao model. Pop-in events occurring at a depth of ~23 nm with indentation loads of 0.60-0.65 mN were confirmed to indicate the elastic-plastic transition of the crystal, on the basis of the Hertzian contact theory and Johnson's cavity model. Theoritically calculated maximum tensile strength (13.5 GPa) and cleavage strength (33 GPa) also affirms the deformation due to the first pop-in rather than tensile stresses. Further analyses of deformation behavior across the indent was done in 4H-SiC by a combined technique of focused ion beam and transmission electron microscope, revealing that slippage occurred in the (0001) plane after indentation.